Analisis Kemampuan Manajerial terhadap Kinerja Bisnis Keluarga dengan Kemampuan Teknologi Informasi sebagai Variabel Intervening - agustinus walansendow (PolimdoSains, 2020)
Analysys of Manajerial Ability in The Family Business Performance with InformationTechnoly Skills as an Intervening Variable: (Study on Craetive Tourism Industry of Handycraft SME’s in North Sulawesi Province. This study examines the effect of manajerial ability on family business performance with information technology skill as an intervening variable of handicraft SME’s in North Sulawesi province. A good SME handycraft business performance will strengthen the existence of SME’s in the domestic market and upgrade the ability to compete equally in the global market. The population of this study is the handycraft business consisting of 77 handycraft business units. The sampling technique used is probability sampling with primary data sourced from SME business owner who know the condition of the use of information technology and managerial ability in managing the business. The method used to analyze the data is Structural Equation Model (SEM) with the aid of smatPls. The results of data analysis show that business performance can be seen from the managerial ability which is 90.60% and managerial ability for information technology at 94.10%. the result of Hypothesis testing show that managerial ability has a positive effect on family business performance and the manager’s ability has a positive effect on information technology skill, but information technology has no effect on business performance of handycratf SME’s in North Sulawesi Province.